Synergistic Effect of Cinnamon (Cinnamomum burmannii) Leaves Extract and Potassium Iodide on Mild Steel in HCl - Rohil; Stiadi, Yeni; Emriadi (Chempublish Journal, 2025)
The synergistic impact of potassium iodide with cinnamon leaf extract (CLE) on hindering gentle steel corrosion in a HCl arrangement was examined utilizing weight loss measurement, UV-Vis spectroscopy, and X-ray diffraction (XRD) analysis. At an inhibitor concentration of 10 g/L CLE coupled with 0.04 g/L potassium iodide, the inhibition efficiency increased from 92.8% to 97.06% as the temperature and concentration increased. The Langmuir adsorption isotherm was followed by the inhibitor's adsorption on the mild steel surface. The synergistic interaction between CLE and potassium iodide was validated when the synergistic parameter (S) was greater than 1. The inhibitor components and the steel surface formed a coordination complex, according to UV-Vis analysis. When CLE was present, a defensive layer formed on the mild steel surface that prevented the corrosive medium from interacting with the metal, as confirmed by XRD analysis. These results imply that potassium iodide and CLE may be useful and sustainable corrosion inhibitors for mild steel in acidic environments